1984
DOI: 10.1002/ijc.2910330208
|View full text |Cite
|
Sign up to set email alerts
|

Endemic Kaposi's sarcoma: Incidence and risk factors in the west Nile district Of Uganda

Abstract: Out of 72 Kaposi's sarcoma patients diagnosed between 1951 and March 1976 at Kuluva Hospital, West Nile District, Uganda, 64 with known co-ordinates were plotted on a map. Sixty-two of these were noted to live at an altitude of 853 metres or more (greater than or equal to 2,800 feet). Twenty-four patients were thought to be still alive and visits were made to their homes. Space-time grouping of four cases was noted on two occasions, although analysis did not reveal statistically significant clustering. A case-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Moreover, about 2 decades ago it was suggested that KS might represent a new model in the search for viruses associated with human malignancies, such as herpesviruses (Giraldo et al, 1972a, b). This was further supported by the identification of clustering (McHardy et al, 1984) and extensive serologic and molecular biologic studies, particularly on AKS (Giraldo et al, 1980(Giraldo et al, , 1989Boldogh et al, 1981). In 1981 a sudden increase in KS among young homosexual men was described in the USA (Friedman-Kien et al, 1981).…”
mentioning
confidence: 77%
“…Moreover, about 2 decades ago it was suggested that KS might represent a new model in the search for viruses associated with human malignancies, such as herpesviruses (Giraldo et al, 1972a, b). This was further supported by the identification of clustering (McHardy et al, 1984) and extensive serologic and molecular biologic studies, particularly on AKS (Giraldo et al, 1980(Giraldo et al, , 1989Boldogh et al, 1981). In 1981 a sudden increase in KS among young homosexual men was described in the USA (Friedman-Kien et al, 1981).…”
mentioning
confidence: 77%
“…While such a hypothesis may fit their observations among homosexual men, African patients with classical KS appear not to be immunosuppressed, judged on the basis of T-lymphocyte subset studies and studies on skin test reactivity to recall antigens and mitogens (Kestens et al, 1985). Furthermore, in Uganda there is a high incidence of classical KS (McHardy et al, 1984), making genetic predisposition in this population a theoretical possibility. However, the number of reported AIDS-associated KS cases has been low despite an ongoing epidemic of HTLV-I11 infection and enteropathic AIDS in this area (Serwadda et al, 1985).…”
Section: Discussionmentioning
confidence: 98%
“…In Europe, elderly men from Mediterranean areas and/or of Ashkenazi Jewish descent have been considered at special risk of non-AIDS-KS (Hutt, 1984;Contu et al, 1984) but no studies have examined this distribution with regard to AIDS-related KS (AIDS-KS). Non-AIDS-KS has also been seen in persons iatrogenically immunosuppressed as part of therapy for cancer or transplantation and is endemic in certain parts of Central Africa where it has a slowly progressive course with a low fatality rate in the majority of cases (McHardy et al, 1984).…”
mentioning
confidence: 99%